1988
DOI: 10.1007/bf03219408
|View full text |Cite
|
Sign up to set email alerts
|

Out of the classroom, into the courts: The legalization of Australian education and its implications for educational research

Abstract: This paper argues, on the basis of comparative research and a study of recent Federal and State statute law and court decisions, that Australian education is becoming legalized. That is, new rights in education are being elaborated. New procedural protections enforced. The rule of law is developing in Australian education, where custom law used to prevail. This, the writers suggest, calls for new items on the educational research agenda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Stewart (1996, Figure 2) has provided a conceptual model of the relationship that exists between the law, specifically parliamentary legislation and decisions of various legal tribunals on the one hand, and school policies and practices on the other. It is worth noting, however, that despite this close relationship, as well as claims by other researchers Sungaila & Swafford, 1987;Williams, 1995) that education in Australia has become legalised to such an extent that it drives massive change to school mission statements, policies and practices, recent research has shown that Australian principals remain woefully uninformed and ill-informed about basic legal matters affecting school operations (Stewart, 1996).…”
Section: Leadership Professional Development and School Lawmentioning
confidence: 94%
“…Stewart (1996, Figure 2) has provided a conceptual model of the relationship that exists between the law, specifically parliamentary legislation and decisions of various legal tribunals on the one hand, and school policies and practices on the other. It is worth noting, however, that despite this close relationship, as well as claims by other researchers Sungaila & Swafford, 1987;Williams, 1995) that education in Australia has become legalised to such an extent that it drives massive change to school mission statements, policies and practices, recent research has shown that Australian principals remain woefully uninformed and ill-informed about basic legal matters affecting school operations (Stewart, 1996).…”
Section: Leadership Professional Development and School Lawmentioning
confidence: 94%